ANALISIS HASIL KEKUATAN TARIK SAMBUNGAN WIRE TERHADAP VARIASI KODE TERMINAL DAN UKURAN WIRE PADA PROSES CRIMPING SEMI OTOMATIS - Irawan Tri Yunanto; Afdhal Kurniawan Mainil; Nurbaiti Nurbaiti (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
This study was conducted to determine the quality of crimped connections in the wire harness manufacturing sector. Three methods were used in the connection process, but this analysis only used the semi automatic crimping method, and in general, the crimping results are applied to electronic devices, therefore the quality of the conection must also be considered carefully and must comply with the crimping specifications. Therefore, the result of this test were analysed to determine the quality of the semi automatic crimping process. The quality of the crimping results is greatly influenced by the combination of terminal type, cable size, and preassure. Meanwhile, the pull force test or pull-out test is used to meanwhile, the mechanical strength of the connection. Then the maximum tensile force value obtained indicates the quality and reliability of the crimped connection. In this study, three types of terminals were used, namely AMP-1318105-1,AMP-175217-5, and AMP-1-175218-5, each of which was combined with wire measuring AWG 24,22, 20, and 18. The test results showed that the combination of the AMP-1-175218-5 terminal with AWG 18 wire produced the highest tensile strength of 15,9 kgf, while the combination of the AMP-1318105-1 terminal with AWG 24 wire produced he lowest tensile strength, but still above the minimum standard that the wire size and type of terminal have a significant influence on the tensile strength of the conection. The larger the wire size, the higher the resulting tensile strength value. Thus, selecting the right combination of terminals and wires is very important to ensure the quality and reliability of electrical connections in the wire harness industry.